Stimulasi Kemampuan Motorik Halus Anak Usia 4-6 Tahun melalui Berbagai Kegiatan di RA Nurhidayah - Zulham Efendi Marpaung; Syazkia Salsabila Rais; Tiara Angelly; Nadya Meilita; Nurlaili Nurlaili (JURNAL EDUKASI NONFORMAL, 2022)
This study aims to stimulate fine motor skills of children aged 4-5 years. The research was conducted on November 7 2022 at RA Nurhidayah. This study uses a qualitative approach with the type of classroom action research (CAR). The classroom action research model used is Kemmis and Mc Taggart which includes four stages, namely: planning, implementing, observing, and reflecting. The research subjects were children aged 4-5 years totaling 21 children consisting of 1 boy and 10 girls. The research data is in the form of qualitative data and the research data sources are teachers and children. The research data were obtained using observation, interview and documentation techniques. Techniques to test the validity of research data using technical triangulation and source triangulation. The research data were analyzed using the interactive Milles and Huberman model which consisted of four stages, namely data collection, data reduction, data presentation and data verification. The results of the research are: stimulation of fine motor skills of children aged 4-6 years through various activities, namely coloring, folding origami, merronce, and collage.